Migrant remittances and diaspora policies in Africa - I. D. Loshkariov; I. S. Kopyttsev (Vestnik MGIMO-Universiteta)
Recent years have seen a substantial increase in remittances from diaspora communities to their home countries, prompting developing economies to establish and enhance institutional mechanisms. These mechanisms aim to channel and leverage the emotional connections of emigrants to their native lands for economic purposes. This article concentrates on the influence of migrant remittances on the formulation of diaspora policies in Africa. It closely examines two clusters encompassing a total of 8 states recognized as leaders in terms of migrant remittances’ share in GDP and their absolute value, respectively. The article evaluates three primary categories of tools and practices that structure diaspora cooperation: formal institutional means, economic tools, and socio-cultural practices. The research applies a neo-institutional approach, conceiving diaspora policy as a network of interconnected practices across various spheres. By comparing cases within and between these clusters, it demonstrates diverse approaches to developing diaspora cooperation mechanisms. Additionally, the authors outline the most promising pathways for advancing diaspora policies while identifying existing barriers.They advocate for the establishment of distinct platforms for diaspora representation, deepening cooperation between origin and host states, and extending certain diaspora policy mechanisms to subnational and supranational levels. However, the development of diaspora politics in the examined cases is impeded by insufficient resources, weak state institutions, and state reluctance to cede control over their population's interaction with external actors. Despite the prevalent notion that the evolution of diaspora cooperation mechanisms correlates with the volume of migrant remittances, empirical analysis within the African context exposes the explanatory limitations of such a model.